2009
DOI: 10.2174/1874915100902010048
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Capital Structure in the Service Industry: Evidence from United States

Abstract: Abstract:The paper seeks to extend Biger, Nguyen, and Hoang' (2008) findings regarding the determinants of capital structure. Empirical results show that that leverage is negatively related to the firm's profitability. This paper offers useful insights for the service industry owner/operators and managers based on empirical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
183
8
26

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(259 citation statements)
references
References 36 publications
42
183
8
26
Order By: Relevance
“…This result is align with the findings by previous researcher such as (Akeem et al, 2014;Ebaid, 2009;Ebrati et al, 2013;Gill, Biger & Mathur, 2011;and John, 2013). In United States, Gill et al (2011) analyse the relationship between the capital structure and firm performance among the American service and manufacturing firms from 2005-2007 and they also found the insignificant relationship between long-term debt to accounting performance in service industry.…”
Section: Capital Structure and Return On Assetsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is align with the findings by previous researcher such as (Akeem et al, 2014;Ebaid, 2009;Ebrati et al, 2013;Gill, Biger & Mathur, 2011;and John, 2013). In United States, Gill et al (2011) analyse the relationship between the capital structure and firm performance among the American service and manufacturing firms from 2005-2007 and they also found the insignificant relationship between long-term debt to accounting performance in service industry.…”
Section: Capital Structure and Return On Assetsupporting
confidence: 93%
“…In United States, Gill et al (2011) analyse the relationship between the capital structure and firm performance among the American service and manufacturing firms from 2005-2007 and they also found the insignificant relationship between long-term debt to accounting performance in service industry. They claim that American firms that operated in service industry recorded a higher gearing ratio.…”
Section: Capital Structure and Return On Assetmentioning
confidence: 99%
“…On the other hand, the static trade-off theory (Myers 1984;Myers and Majluf 1984) provides a contradictory view and argues that profitable firms have greater needs to shield income from corporate tax to increase profits and should borrow more as compared to less profitable firms. In contrast to Myers and Majluf (1984) and Myers' (1984) views, empirical evidence from financial and non-financial firms Gill et al 2009;Najjar and Petrov 2011;Rajan and Zingales 1995;Sharif et al 2012;Teker et al 2009) found that profitable firms used less debt financing in line with the pecking order theory, while studies by Kumar et al (2012) and Sayeed (2011) found that profitable firms used more debt finance. As a proxy for the measure of profitability, our study used the ratio of operating income to total assets (return on assets) used by Booth et al (2001), Cassar and Holmes (2003), Mohammed Amidu (2007), and Adesola (2009).…”
Section: Empirical Review and Conceptual Frameworkmentioning
confidence: 88%
“…They stated a negative relationship between the profitability and debt across the enterprises in the forest industry. On the contrary, Gill et al (2011) concluded that there is a positive relationship between the shortterm debt to the total assets and profitability, between the long-term debt to the total assets and profitability and between the total debt to the total assets and profitability in the manufacturing industry. Also Abor (2005) contend that there is a positive relation between the ratio of the short-term debt to the total assets and profitability and a negative relationship between the ratio of long-term debt to the total assets and the return on equity.…”
Section: Discussionmentioning
confidence: 98%